The Creation of Foundations, Beginnings and Early Development of the University of Maribor - Melanšek, Tadeja; Friš, Darko (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2026)
The development of higher education in Maribor was closely tied to educational reforms in Slovenia and Yugoslavia, as well as to the economic and social needs of northeastern Slovenia after the Second World War. Between 1959 and 1961, the first higher education institutions were established in Maribor, including schools of commerce, engineering, agronomy, law, dentistry, and the Pedagogical Academy. In 1961, the Association of Higher Education Institutions in Maribor was also founded, representing a significant step toward the institutional integration of the higher education landscape. In the early 1970s, with support from both local and republican authorities, intensive preparations for the establishment of a university began. The self-management agreement to merge into the University of Maribor was signed on June 12, 1975, and confirmed by the Assembly of the Socialist Republic of Slovenia on July 2, 1975. This officially marked the founding of the University of Maribor, with Vladimir Bračič serving as its first rector.